A taxonomic and distributional study of the rhodolith-forming species Lithothamnion muelleri (Corallinales, Rhodophyta) in the Eastern Pacific Ocean - Robinson, Néstor M. (2013)
Lithothamnion muelleri is reported for the first time as one of the main components of rhodolith beds along the Eastern Pacific Ocean based on samples from Washington State (USA), Pacific Baja California (México), southern Nicaragua, and Costa Rica. Individual rhodoliths ranged from fruticose to lumpy in morphology, and bi-sporangial, tetrasporangial, and gametangial plants were similar to those described from Australia and Brazil. Our study revealed a surprisingly wide latitudinal distribution of this species along the American continent. Its documentation in the Eastern Pacific will facilitate a more accurate interpretation of the ecology, biology, and biogeography of rhodolith beds worldwide.